Molecular characterization of six unrelated Italian patients affected by pyrimidine 5′‐nucleotidase deficiency - Bianchi, Paola; Fermo, Elisa; Alfinito, Fiorella; Vercellati, Cristina; Baserga, Mariangiola; Ferraro, Filomena; Guzzo, Immacolata; Rotoli, Bruno; Zanella, Alberto (British journal of haematology, 2003)
Pyrimidine 5′‐nucleotidase deficiency is a rare autosomal recessive disorder characterized by haemolytic anaemia, marked basophilic stippling and accumulation of pyrimidine nucleotides within the erythrocytes. The gene encoding for this enzyme (P5′N‐1) has been cloned recently, and seven mutations have so far been identified in 11 unrelated families. We describe the haematological and molecular characteristics of six unrelated Italian patients affected by pyrimidine 5′‐nucleotidase deficiency (one from northern and five from southern Italy). The sequence of the complete P5′N‐1 gene showed the presence of four different new mutations: a missense mutation AAT–AGT at codon 190 (Asn–Ser), one splicing mutation (IVS9‐1 g‐c) and two frameshift mutations, DelG576 and InsGG743. Although the molecular defect was homozygous in all patients but one, parents' consanguinity could be confirmed in only one case. InsGG743 was detected in two cases, and DelG576 was found in three patients originating from southern Italy, suggesting a possible geographical distribution of the genetic defect. Haematological data showed the presence of peripheral spherocytosis in all cases, although only one had a concomitant membrane defect. An increase in serum ferritin levels was observed in the splenectomized patients, suggesting that the iron status of these subjects should be monitored and that they should be investigated for potential additional risk factors for iron accumulation.